(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
Today, when assessing the development level of each country, the development level of infrastructure is a crucial indicator. Therefore, investment in the development of production infrastructure is a priority and goes ahead of direct investment. Along with labor, capital, natural resources, etc., science and technology are considered essential resources with a significant impact on economic development. Over 35 years of innovation, our country’s science and technology have made positive changes with many achievements in research and investigation, creating a scientific basis for formulating strategies and plans for economic development. Socio-economic, environmental protection, science, and technology, in association with production and life, contribute to improving productivity, quality, and efficiency of all branches and fields.